2021
DOI: 10.3389/fonc.2021.705547
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Novel Methylation-Driven Gene Model and Investigation of PARVB Function in Glioblastoma

Abstract: BackgroundGlioblastoma multiforme (GBM) is characterized by widespread genetic and transcriptional heterogeneity. Aberrant DNA methylation plays a vital role in GBM progression by regulating gene expression. However, little is known about the role of methylation and its association with prognosis in GBM. Our aim was to explore DNA methylation-driven genes (DMDGs) and provide evidence for survival prediction and individualized treatment of GBM patients.MethodsUse of the MethylMix R package identified DMDGs in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Methylation of UPP1 was confirmed as a prognostic factor for GBM multiforme in two bioinformatics analyses (Weng and Salazar, 2021;Yu et al, 2021). UPP1 is a potential biomarker of thyroid cancer, and the possible mechanism of regulating epithelialmesenchymal transition (EMT) plays the role of oncogene (Guan et al, 2019).…”
Section: Figurementioning
confidence: 89%
“…Methylation of UPP1 was confirmed as a prognostic factor for GBM multiforme in two bioinformatics analyses (Weng and Salazar, 2021;Yu et al, 2021). UPP1 is a potential biomarker of thyroid cancer, and the possible mechanism of regulating epithelialmesenchymal transition (EMT) plays the role of oncogene (Guan et al, 2019).…”
Section: Figurementioning
confidence: 89%
“…Furthermore, studies have reported that GBM patients with MGMT methylation are more sensitive to chemo‐radiotherapy and show a better survival advantage 24 . Recent studies have demonstrated the impact of DNA methylation‐driven alterations on the occurrence and progression of GBM 15,25,26 . The integrated analysis of DNA methylation and gene expression profiles can better analyze the regulatory function of methylation and molecular mechanisms of tumors 14,27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies mainly focused on single omics and often neglected the complexity of the molecular‐based phenomena landscape 12,13 . To better indicate the transcriptional regulation function of DNA methylation and elucidate the pathogenesis and molecular mechanisms of GBM, recent studies integrated the profiles of DNA methylation and mRNA expression to recognize driven methylated specific genes that are capable of regulating gene expression in cancer, including GBM methylation‐driven genes 14,15 . However, genes for both early diagnosis and prognosis based on DNA methylation‐driven patterns have not been explored for GBM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation signature has been reported to be associated with survival in glioma, for example, a two-CpG site DNA methylation signature was constructed to predict the prognosis of lower-grade glioma with high accuracy ( Guo W. et al, 2022 ). Additionally, a DNA methylation-driven genes signature was established for risk stratification in GBM ( Yu et al, 2021 ). m6A RNA methylation was reported to regulate the tumorigenesis of glioma.…”
Section: Discussionmentioning
confidence: 99%